Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.46281/aijssr.v6i1.931
|View full text |Cite
|
Sign up to set email alerts
|

Afghan Students’ Satisfaction From Online Learning During Covid-19 at Kandahar University, Kandahar, Afghanistan

Abstract: This purpose of this study was to examine the satisfaction of Afghan students from online learning during COVID-19 at Kandahar University, Kandahar, Afghanistan. This research used a quantitative approach, and the learners were from several departments of Education Faculty as well as they were selected through random sample. Similarly, the questionnaire was the main instrument of this study. As well as, three hundred and forty students took participation. After collecting the data, it was analyzed by implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 17 publications
4
17
0
Order By: Relevance
“…Almost all students found online learning less useful and preferred returning to campus-based face-to-face education. Other studies conducted with Afghan university students also confirmed the dissatisfaction students expressed with online learning in this study (Hashimi, 2021;Himat et al, 2021). Likewise, survey data from 878 higher education stakeholders, with 81.7% comprising university students from various discipline areas, in India showed that 86.3% of the respondents preferred face-to-face education over online education (Nail et al, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…Almost all students found online learning less useful and preferred returning to campus-based face-to-face education. Other studies conducted with Afghan university students also confirmed the dissatisfaction students expressed with online learning in this study (Hashimi, 2021;Himat et al, 2021). Likewise, survey data from 878 higher education stakeholders, with 81.7% comprising university students from various discipline areas, in India showed that 86.3% of the respondents preferred face-to-face education over online education (Nail et al, 2021).…”
Section: Discussionsupporting
confidence: 81%
“…The results of the current research agree with several study results indicating students' satisfaction with online courses (Ali, 2021;Al-Kaf & Al-Balushi, 2021;Chanchalor & Powichai, 2003;Hazeri & Farzin-Yazdi, 2015;Kahawan, 2014;Manhray, 2015;Ong & Lai, 2006;Sharhan, 2003). However, these results, along with other results, indicate that students are not satisfied with the experience of ecourses in general and the distance field training in particular (Himat et al, 2021;Shehat & Al-Amri, 2022).…”
Section: Discussionmentioning
confidence: 73%
“…Access to adequate broadband and suitable study spaces was identified in this study and in other explorations of the pandemic student experience (Himat et al, 2020;Neuwirth, 2020;), and although this may impact all students it is likely to be a more significant challenge for students from equity groups. Inequalities in access to online teaching have been identified as a concern amongst school leaders (Trinidad, 2021) and in the context of HE a survey commissioned by the UK regulator found "a significant number of students whose access to remote education is being disruptedsometimes severelyby poor access to core digital infrastructure" (Office for Students, 2020d, np), setting up a review of students' digital poverty as a result.…”
Section: Online Teaching and Assessmentmentioning
confidence: 75%